Control-oriented modelling and simulation of thrust misalignment and wind disturbances for hypersonic vehicles. (1st January 2013) - Du, Yanli; Lu, Yuping; Wu, Qingxian; Jiang, Changsheng
Near-space hypersonic vehicles (NHVs) are viewed as reliable, affordable and global reach vehicles. Their controller design is a challenging task due to strong uncertainties and disturbances in the flight dynamics of NHVs. In this paper, a new methodology is presented to build control-oriented models of two kinds of disturbances. For a winged-cone NHV, the paper models the moment disturbance induced by the thrust misalignment of the engine. Next, a new group of 12-state equations is obtained based on the kinetic and dynamic laws for the NHV with variable wind field, as the wind turbulence frequently occur in the upper near space. Then, the quantisation and simulation results about the models are provided to show the variation characteristics of the disturbances. Finally, the attitude control results are given to assess the adaptive control effect of the NHV with these two models. Therefore, in the presence of the thrust misalignment and wind disturbances, the control-oriented models presented can become the simulation tools which help us to evaluate adaptive control laws designed for NHVs.